REALISASI TINDAK PENGANCAM MUKA (FACE-THREATENING ACT) PADA DEKLARASI KEMENANGAN PILPRES 2019 BERDASARKAN HASIL HITUNG CEPAT LEMBAGA SURVEI - Ahmad Fadly (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
Politicians, especially those who are running for president, are very influential for their supporters. How to speak is often a role model for his followers. In fact, his orders and prohibitions were strongly held by his sympathizers. In addressing the differences in quick count results between several survey institutions and the results of internal surveys triggering a declaration of victory by each presidential candidate. Submission of directive instructions to their supporters is very important, especially in terms of face-threatening acts. This research used qualitative approach. The data used in this study are four video declarations of victory (two video declarations of victory by presidential election candidate number 01 and two video victory declarations by presidential election candidate number 02). This study resulted in two strategies of directive speech action applied by pair serial number 01, namely clearly speaking plus positive politeness and speaking vaguely. The strategies applied by the 02 presidential candidate are twofold, namely to speak frankly and speak clearly plus positive politeness. In terms of quantity, the directive of presidential candidate number 01 numbered six utterances, while the candidate number 02 numbered 13 speeches (acts)